Source/drain electrodes contact effect on the stability of bottom-contact pentacene field-effect transistors - Xinge Yu; Junsheng Yu; Wei Huang; Lin Zhang; Hongjuan Zeng (AIP Advances, 2012)
Bottom-contact pentacene field-effect transistors were fabricated with a PMMA dielectric layer, and the air stability of the transistors was investigated. To characterize the device stability, the field-effect transistors were exposed to ambient conditions for 30 days and subsequently characterized. The degradation of electrical performance was traced to study the variation of field-effect mobility, saturation current and off-state current. By investigating the morphology variance of the pentacene film at the channel and source/drain (S/D) contact regions by atomic force microscopy, it was clear that the morphology of the pentacene film adhered to the S/D degenerated dramatically. Moreover, by studying the variation of contact resistance in detail, it was found that the S/D contact effect was the main reason for the degradation in performance.